Healthcare workers' perceptions and experience of primary healthcare integration: a qualitative evidence synthesis - Moloi, Hlengiwe (Cochrane Database Syst Rev, 2020)
This is a protocol for a Cochrane Review (qualitative). The objectives are as follows: To identify, appraise, and synthesise qualitative studies exploring healthcare workers' perceptions and experiences of PHC integration; to identify the factors influencing healthcare workers' perceptions and experiences of PHC integration interventions; and to guide an update of the Cochrane PHC integration effectiveness review (Dudley 2011), by identifying contextual variation that may be associated with variation in effectiveness.